PENGARUH METODE PEMBELAJARAN MIND MAPPING TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN TATA KELOLA HUMAS DAN PROTOKOLER KELAS XII SMK DAARUL FATAA BOJONGGEDE - BOGOR - Waspada Waspada (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2020)
One of the successness of learning is difined by the method which being utilized in learning process. Many learning methods are being developed by the education experts in case to encourage the successness learning, one of them is the Mind Mapping method. Mind Mapping could be said to be relatively new learning method.Mind Mapping method in education is a way of serving and delivery learning materials which teacher give the opportunities to the students whether individually or in a group to conduct the scientif talk in terms of collecting views, and make the conclusion or arrange any alternative problem solving, Mind Mapping is a way learning serving, where students are faced to any problem. (Problem solving). This study found that there is an influence of Mind Mapping learning method in increasing students learning achievements in the subjects of human governance and protocol for XII grade at SMK Daarul Fataa Bojonggede, Bogor. To strengthen this study, researcher conducted instrument testing , where the instrument testing showed there is a significant influence in utilizing mind mapping learning method in increasing student learning achievement in the subjects of human governance and protocol.